THE EFFECT OF MANAGERIAL OWNERSHIP, INSTITUTIONAL OWNERSHIP AND AUDIT COMMITTEE ON TAX AVOIDANCE IN MINING COMPANIES LISTED ON THE IDX IN 2017-2020 - Ridhawati, Rakhmi; Mulyani, Sri (Universitas Muhammadiyah Kalimantan Timur, 2022)
This study aims to empirically prove the effect of managerial ownership, institutional ownership and audit committee on tax avoidance in mining companies listed on the Indonesia Stock Exchange in 2017-2020. The research method used is a quantitative method. Data collection method in this study was documentation from secondary data available on Indonesian Stock Exchange website. This study used multiple regression analysis as statistical tools to test the research hypotheses. The results show that managerial ownership, institutional ownership and audit committee have no effect on tax avoidance either partially or simultaneously.